Activation of Vitamin D Regulates Response of Human Bronchial Epithelial Cells to Aspergillus fumigatus in an Autocrine Fashion - Pei Li; Ting Wu; Xin Su; Yi Shi (Mediators of Inflammation)
Aspergillus fumigatus (A. fumigatus) is one of the most common fungi to cause diseases in humans. Recent evidence has demonstrated that airway epithelial cells play an important role in combating A. fumigatus through inflammatory responses. Human airway epithelial cells have been proven to synthesize the active vitamin D, which plays a key role in regulating inflammation. The present study was conducted to investigate the impact of A. fumigatus infection on the activation of vitamin D and the role of vitamin D activation in A. fumigatus-elicited antifungal immunity in normal human airway epithelial cells. We found that A. fumigatus swollen conidia (SC) induced the expression of 1α-hydroxylase, the enzyme catalyzing the synthesis of active vitamin D, and vitamin D receptor (VDR) in 16HBE cells and led to increased local generation of active vitamin D. Locally activated vitamin D amplified SC-induced expression of antimicrobial peptides in 16HBE cells but attenuated SC-induced production of cytokines in an autocrine fashion. Furthermore, we identified β-glucan, the major A. fumigatus cell wall component, as the causative agent for upregulation of 1α-hydroxylase and VDR in 16HBE cells. Therefore, activation of vitamin D is inducible and provides a bidirectional regulation of the responses to A. fumigatus in 16HBE cells.